Kecerdasan Majemuk dalam Perspektif Psikologi Pendidikan Agama Islam: Integrasi Teori Gardner dengan Nilai-Nilai Islam - Yulqowin, Ilma; Purwoyulianto, Heru; Rohimah, Siti (Lembaga Yasin AlSys, 2025)
This study explores the integration of the Multiple Intelligences theory developed by Howard Gardner with the concept of Islamic Educational Psychology. Gardner’s theory emphasizes that human intelligence is multifaceted, encompassing linguistic, logical-mathematical, spatial, bodily-kinesthetic, musical, interpersonal, intrapersonal, naturalistic, and existential/spiritual dimensions. In Islamic thought, intelligence is viewed as fitrah, an innate potential bestowed by Allah, which must be developed in a balanced manner to achieve the goal of Islamic education: the formation of insan kamil (a complete and virtuous human being). This study aims to analyze the correlation between the dimensions of intelligence in Gardner’s theory and the concept of intelligence as conveyed in the Qur’an and Hadith, and to formulate instructional strategies aligned with Islamic values. A qualitative content analysis method was employed, drawing from both primary and secondary sources. The findings reveal a strong alignment between the concept of multiple intelligences and the principles of Islamic education, underscoring the importance of a holistic instructional approach that accommodates the diverse potentials of learners. The study also presents practical examples of learning activities to support integrative implementation in the classroom. In conclusion, integrating the Multiple Intelligences theory with Islamic Educational Psychology can enhance the effectiveness of learning processes that are not only cognitive but also spiritual and moral in nature.